Telemedicine in humanitarian aid: evaluation of potentials and challenges and an implementation trial in Ukraine - Habers, Florian; Müller, Anna; Kunczik, Janosch; Rossaint, Rolf; Czaplik, Michael; Follmann, Andreas (Frontiers in Disaster and Emergency Medicine, 2025)
IntroductionProviding health care in humanitarian aid missions and conflict settings, such as the ongoing war in Ukraine, presents significant logistical and operational challenges. Telemedicine has emerged as a promising tool to support medical personnel in such environments.MethodsThis study developed a concept for a telemedicine system tailored to humanitarian aid missions. A functioning telemedicine service was implemented and tested under simulated conditions, and its acceptance among medical professionals was assessed through a structured survey.ResultsThe survey revealed high levels of interest and acceptance of telemedicine among medical staff, indicating strong potential for practical application. Key barriers and limitations—such as connectivity issues, training needs, and integration challenges—were identified and analyzed.ConclusionsFor effective implementation of telemedicine in humanitarian settings, a detailed needs analysis and close integration with existing health care infrastructure are essential. Strategic recommendations are provided to guide future deployments and improve service delivery in conflict zones.